Students Learning Processes on Measures of Central Tendency in Senior High School Classrooms Based on the Theory of Didactical Situations - Wulan Putri Utami; Mohamad Gilar Jatisunda (Didaktik Matematika, 2025)
In the current data-driven society, developing a deep understanding of statistical concepts is essential for students to interpret and communicate quantitative information effectively. This study explores how students construct a sense of the measures of central tendencymean, median, and modethrough interactions within didactical situations designed according to the Theory of Didactical Situations (TDS). Using an exploratory case study, sixteen tenth-grade senior high school students participated in two instructional sessions structured around five TDS phases: devolution, action, formulation, validation, and institutionalisation. Data were collected through observations, video recordings, written work, and field notes, and analyzed using deductive content analysis guided by the TDS framework. The findings reveal that learning structured around TDS phases fosters the emergence of intuitive strategies and promotes conceptual understanding of mean, median, and mode. Students gradually shifted from procedural computation toward reflective reasoning and contextual interpretation. This study contributes to mathematics education by demonstrating how TDS-based instruction can foster epistemic autonomy and conceptual growth in statistical learning